1990
DOI: 10.1111/j.1471-0528.1990.tb02497.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial, physical and psychological effects of postmenopausal oestrogen therapy with added dydrogesterone

Abstract: Summary. Sixteen postmenopausal women receiving conjugated equine oestrogens 1.25 mg/day. continuously, were randomly allocated to add dydrogesterone 20 mg/day for 12 days each calendar month for 3 months and then 10 mg/day in an identical fashion for a further 3 months, or to receive the dydrogesterone doses in reverse sequence. The effects of the two dydrogesterone doses on endometrial histology, vaginal bleeding, and the symptomatic and psychological status were compared. Endometrial samples were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Acceptable withdrawal bleeds with low rates of noncyclic bleeding have been shown in previous studies using dydrogesterone (Caudron & Hendrickx 1988; Coutts et al 1983; De Cleyn et al 1986; Lane et al 1986; Rees et al 1991; Siddle et al 1990b). This present study confirms these findings in a larger number of subjects.…”
Section: Discussionmentioning
confidence: 70%
“…Acceptable withdrawal bleeds with low rates of noncyclic bleeding have been shown in previous studies using dydrogesterone (Caudron & Hendrickx 1988; Coutts et al 1983; De Cleyn et al 1986; Lane et al 1986; Rees et al 1991; Siddle et al 1990b). This present study confirms these findings in a larger number of subjects.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, improvement of mood symptoms and anxiety after DYD administration (18)(19)(20) can be dependent, at least in part, on an increased level of allopregnanolone.…”
Section: Discussionmentioning
confidence: 94%
“…The administration of DYD in fertile women affected by moderate to severe premenstrual syndrome was more effective than placebo against psychological symptoms such as anxiety, tension, and irritability (18). The reduction of anxiety scores in postmenopausal women was greater in those receiving a sequential regimen of transdermal estradiol plus DYD than in those receiving norethisterone acetate (NETA) or nomegestrol acetate (NMA) (19), without affecting negatively the reduction of the depression score induced by the administration of estradiol (20). Several lines of evidence suggest that a drop of 5a-reduced metabolites of progesterone plays a pivotal role in the physiopathology of central nervous system-related symptoms of premenstrual syndrome, premenstrual dysphoric disorder, and menopausal transition.…”
Section: Discussionmentioning
confidence: 98%
“…79, 1115, 17, 18 The only large intervention study that has specifically investigated the mood effects of progestins found no effect of a variety of progestin preparations on mood in a sample of non-depressed women. 16 It is also notable that our depressed study population had BDI scores within the mild-to-moderate range of depressive symptoms at baseline, which were subsequently reduced to minimal-to-mild levels on ET and then remained minimal-to-mild on MPA.…”
Section: Discussionmentioning
confidence: 99%